A BaSiC tool for background and shading correction of optical microscopy images - Tingying Peng (Nature Portfolio, 2017)
Accurate quantification of bioimaging data is often confounded by uneven illumination (shading) in space and background variation in time. Here the authors present BaSiC, a Fiji plugin solving both issues. It requires fewer input images and is more robust to artefacts than existing shading correction tools.